Pt/ZrO2 Prepared by Atomic Trapping: An Efficient Catalyst for the Conversion of Glycerol to Lactic Acid with Concomitant Transfer Hydrogenation of Cyclohexene - Tang, Zhenchen; Liu, Pei; Cao, Huatang; Bals, Sara; Heeres, Hero J; Pescarmona, Paolo P (ACS catalysis, 2019)
A series of heterogeneous catalysts consisting of highly dispersed Pt nanoparticles supported on nanosized ZrO2 (20 to 60 nm) was synthesized and investigated for the one-pot transfer hydrogenation between glycerol and cyclohexene to produce lactic acid and cyclohexane, without any additional H2. Different preparation methods were screened, by varying the calcination and reduction procedures with the purpose of optimizing the dispersion of Pt species (i.e., as single-atom sites or extra-fine Pt nanoparticles) on the ZrO2 support. The Pt/ZrO2 catalysts were characterized by means of transmission electron microscopy techniques (HAADF-STEM, TEM), elemental analysis (ICP-OES, EDX mapping), N2-physisorption, H2 temperature-programmed-reduction (H2-TPR), X-ray photoelectron spectroscopy (XPS), and X-ray diffraction (XRD). Based on this combination of techniques it was possible to correlate the temperature of the calcination and reduction treatments with the nature of the Pt species. The best catalyst consisted of subnanometer Pt clusters (<1 nm) and atomically dispersed Pt (as Pt2+ and Pt4+) on the ZrO2 support, which were converted into extra-fine Pt nanoparticles (average size = 1.4 nm) upon reduction. These nanoparticles acted as catalytic species for the transfer hydrogenation of glycerol with cyclohexene, which gave an unsurpassed 95% yield of lactic acid salt at 96% glycerol conversion (aqueous glycerol solution, NaOH as promoter, 160 °C, 4.5 h, at 20 bar N2). This is the highest yield and selectivity of lactic acid (salt) reported in the literature so far. Reusability experiments showed a partial and gradual loss of activity of the Pt/ZrO2 catalyst, which was attributed to the experimentally observed aggregation of Pt nanoparticles.A series of heterogeneous catalysts consisting of highly dispersed Pt nanoparticles supported on nanosized ZrO2 (20 to 60 nm) was synthesized and investigated for the one-pot transfer hydrogenation between glycerol and cyclohexene to produce lactic acid and cyclohexane, without any additional H2. Different preparation methods were screened, by varying the calcination and reduction procedures with the purpose of optimizing the dispersion of Pt species (i.e., as single-atom sites or extra-fine Pt nanoparticles) on the ZrO2 support. The Pt/ZrO2 catalysts were characterized by means of transmission electron microscopy techniques (HAADF-STEM, TEM), elemental analysis (ICP-OES, EDX mapping), N2-physisorption, H2 temperature-programmed-reduction (H2-TPR), X-ray photoelectron spectroscopy (XPS), and X-ray diffraction (XRD). Based on this combination of techniques it was possible to correlate the temperature of the calcination and reduction treatments with the nature of the Pt species. The best catalyst consisted of subnanometer Pt clusters (<1 nm) and atomically dispersed Pt (as Pt2+ and Pt4+) on the ZrO2 support, which were converted into extra-fine Pt nanoparticles (average size = 1.4 nm) upon reduction. These nanoparticles acted as catalytic species for the transfer hydrogenation of glycerol with cyclohexene, which gave an unsurpassed 95% yield of lactic acid salt at 96% glycerol conversion (aqueous glycerol solution, NaOH as promoter, 160 °C, 4.5 h, at 20 bar N2). This is the highest yield and selectivity of lactic acid (salt) reported in the literature so far. Reusability experiments showed a partial and gradual loss of activity of the Pt/ZrO2 catalyst, which was attributed to the experimentally observed aggregation of Pt nanoparticles.